Aluminum toxicity and aluminum stress-induced physiological tolerance responses in higher plants. (4th July 2021) - Chauhan, Devendra Kumar; Yadav, Vaishali; Vaculík, Marek; Gassmann, Walter; Pike, Sharon; Arif, Namira; Singh, Vijay Pratap; Deshmukh, Rupesh; Sahi, Shivendra; Tripathi, Durgesh Kumar
Abstract: Aluminum (Al) precipitates in acidic soils having a pH < 5.5, in the form of conjugated organic and inorganic ions. Al-containing minerals solubilized in the soil solution cause several negative impacts in plants when taken up along with other nutrients. Moreover, a micromolar concentration of Al present in the soil is enough to induce several irreversible toxicity symptoms such as the rapid and transient over-generation of reactive oxygen species (ROS) such as superoxide anion (O2 −), hydrogen peroxide (H2 O2 ), and hydroxyl radical (OH), resulting in oxidative bursts. In addition, significant reductions in water and nutrient uptake occur which imposes severe stress in the plants. However, some plants have developed Al-tolerance by stimulating the secretion of organic acids like citrate, malate, and oxalate, from plant roots. Genes responsible for encoding such organic acids, play a critical role in Al tolerance. Several transporters involved in Al resistance mechanisms are members of the Aluminum-activated Malate Transporter ( ALMT), Multidrug and Toxic compound Extrusion ( MATE ), ATP-Binding Cassette (ABC ), Natural resistance-associated macrophage protein ( Nramp ), and aquaporin gene families. Therefore, in the present review, the discussion of the global extension and probable cause of Al in the environment and mechanisms of Al toxicity in plants are followed by detailed emphasis on tolerance mechanisms. We have also identified and categorized the important transporters that secrete organic acids and outlined their role in Al stress tolerance mechanisms in crop plants. The information provided here will be helpful for efficient exploration of the available knowledge to develop Al tolerant crop varieties.